Environmental Politics: Waste, Stool, and Disciplinary Effort of the Surabaya Society, 1920s-1940s - Sarkawi B Husain; Agus Indiyanto; Eni Sugiarti (Paramita: Historical Studies Journal, 2023)
The colonial government's hopes to create a rest and order in its colonies proved unsuccessful. The instruments used are not able to force the public to be disciplined. Surabaya, the locus of this article, is not only interesting in a geographical sense, because of its position as a colonial city, but also because colonial governance practices take place intensively in this city. This study aims to complete the aspects that still neglect the attention of scholars by examining the practice of colonial governance to discipline the people of Surabaya through waste and excrement management. In addition to mapping the government policies in waste and excrement management, this article also analyzes why the colonial government failed to discipline the community. This study relies on primary sources in the form of newspapers published during the colonial period. The collected data was analyzed by following three stages, namely reduction, display, and data verification. This article concludes that the community's violation of colonial government rules in waste and excrement management shows the failure of colonial governance practices in disciplining the community. This community disobedience also reflects the public's distrust of the apparatus that carries out the rules. This study also shows that the repressive attitude of the colonial government in implementing environmental hygiene rules reflects awareness among Europeans about the importance of environmental health which is in line with public health.Harapan pemerintah kolonial untuk menciptakan keamanan dan ketertiban di koloninya terbukti tidak berhasil. Instrumen yang digunakan tidak mampu memaksa masyarakat untuk disiplin. Surabaya yang menjadi lokus artikel ini tidak hanya menarik dalam arti geografis, karena posisinya sebagai kota kolonial, tetapi juga karena praktik pemerintahan kolonial berlangsung intensif di kota ini. Penelitian ini bertujuan untuk melengkapi aspek-aspek yang masih diabaikan oleh para sarjana dengan mengkaji praktik pemerintahan kolonial dalam upaya mendisiplinkan masyarakat Surabaya melalui pengelolaan sampah dan kotoran (tinja). Selain memetakan kebijakan pemerintah dalam pengelolaan sampah dan kotoran (tinja), artikel ini juga menganalisis mengapa pemerintah kolonial gagal mendisiplinkan masyarakat. Penelitian ini menggunakan sumber-sumber primer dalam bentuk surat kabar yang diterbitkan pada masa kolonial. Data yang terkumpul dianalisis dengan mengikuti tiga tahap, yaitu reduksi, display, dan verifikasi data. Artikel ini menyimpulkan bahwa pelanggaran masyarakat terhadap aturan pemerintah kolonial dalam pengelolaan sampah dan kotoran menunjukkan kegagalan praktik tata kelola kolonial dalam mendisiplinkan masyarakat. Ketidaktaatan masyarakat ini juga mencerminkan ketidakpercayaan masyarakat terhadap aparatur yang menjalankan aturan. Penelitian ini juga menunjukkan bahwa sikap represif pemerintah kolonial dalam menerapkan aturan kebersihan lingkungan mencerminkan kesadaran bagi masyarakat Eropa tentang pentingnya kesehatan lingkungan yang sejalan dengan kesehatan masyarakat.